Alkyl Polyglucoside (APG) Nonionic Surfactant-Based Reverse Micellar Dyeing of Cotton Fabric – A Study of Reactive Dyes with Different Functional Groups. Issue 1 (31st December 2023) - Tang, Yiu Lun Alan; Lee, Cheng Hao; Chan, Chiu Yuk; Wang, Yanming; Kan, Chi-Wai
ABSTRACT: Reverse micellar dyeing of cotton woven fabrics with natural and biodegradable alkyl polyglucoside-based (APG-based) nonionic surfactant in decamethylcyclopentasiloxane (D5) non-aqueous medium with reactive dyes of different functional groups was investigated and compared with conventional aqueous water-based dyeing in terms of reflectance, color yield, levelness, CIE L*a*b* values, washing fastness and color fading properties. Experimental results have revealed that APG reverse micellar method can provide a higher color yield (K/Ssum value) and lower color reflectance (better dye uptake) than conventional water-based method, along with comparable washing fastness, leveling and color fading properties. Hetero-bifunctional reactive dyes can attain the highest color yield, followed by homo-bifunctional reactive dyes and mono-functional reactive dyes. Mono-functional reactive dyes and homo-bifunctional reactive dyes produce the best levelling properties with smallest levelness variation when compared with that of hetero-bifunctional reactive dyes in non-aqueous D5 dyeing medium.